2018
DOI: 10.3390/pharmaceutics10010034
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Modified Nanocarriers for Nose-to-Brain Delivery: From Bioadhesion to Targeting

Abstract: In the field of nasal drug delivery, nose-to-brain delivery is among the most fascinating applications, directly targeting the central nervous system, bypassing the blood brain barrier. Its benefits include dose lowering and direct brain distribution of potent drugs, ultimately reducing systemic side effects. Recently, nasal administration of insulin showed promising results in clinical trials for the treatment of Alzheimer’s disease. Nanomedicines could further contribute to making nose-to-brain delivery a re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
144
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 243 publications
(147 citation statements)
references
References 174 publications
(192 reference statements)
2
144
0
1
Order By: Relevance
“…One possibility in this context is the use of nanoparticles or liposomes as vehicles, which may improve pharmacokinetic properties and bioavailability of the compounds. 39 Provided that the data obtained by studying additional parameters of Activin A and SerpinB2 application in mice faithfully reflect the situation in humans, such information may help predict therapeutic benefits in realistic clinical settings where the start of treatment after disease onset is variable.…”
Section: Therapeutic Time Window and Clinical Applicationsmentioning
confidence: 99%
“…One possibility in this context is the use of nanoparticles or liposomes as vehicles, which may improve pharmacokinetic properties and bioavailability of the compounds. 39 Provided that the data obtained by studying additional parameters of Activin A and SerpinB2 application in mice faithfully reflect the situation in humans, such information may help predict therapeutic benefits in realistic clinical settings where the start of treatment after disease onset is variable.…”
Section: Therapeutic Time Window and Clinical Applicationsmentioning
confidence: 99%
“…This will let particles diffuse according to their charge or/and polarity. It has been observed that by developing small nanocarriers combined with an encapsulating polymer, it is possible to increase the diffusion in the mucus (Sonvico et al, 2018). Indeed, polymers such as polyethylene glycols allow particles to avoid interactions with mucus mucins and thus to achieve a better mucopenetration.…”
Section: Evaluation Of the Mucoadhesionmentioning
confidence: 99%
“…A few reviews have addressed in detail the formulation aspect of nasal administration, with a special focus on: nanocarriers for nose-tobrain delivery (Sonvico et al, 2018), nasal powders (Tiozzo Fasiolo et al, 2018), mucoadhesive polymers (Chaturvedi et al, 2011), nasal formulation parameters (Dondeti et al, 1996), chitosan for nasal formulations (Casettari and Illum, 2014) and the nasal delivery of high molecular weight drugs (Ozsoy et al, 2009). Besides the formulation aspect, nasal delivery requires a device to aerosolize the formulation to allow its deposition in the nasal cavity.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, NP may offer improved drug delivery to the brain since they can prevent extracellular transport by P-glycoprotein (P-gp) efflux proteins localized in the olfactory epithelium and the endothelial cells that surround the olfactory bulb [114,115]. Additionally, the nanocarriers may also have their functionalized surface with specific ligands to transport agents even more effectively through the BBB [116]. [134].…”
Section: Drug Delivery Systems For Nose-to-brain Delivery In Glioblasmentioning
confidence: 99%